2018
DOI: 10.1097/wnr.0000000000001038
|View full text |Cite
|
Sign up to set email alerts
|

The effects of treadmill exercise on autophagy in hippocampus of APP/PS1 transgenic mice

Abstract: The β-amyloid (Aβ) deposition is one of the major pathological hallmark of Alzheimer’s disease. Dysfunction in autophagy has been reported to lead to the Aβ deposition. The current study aimed to investigate the effects of treadmill exercise on autophagy activity and the Aβ deposition and to demonstrate whether exercise-induced reduction in the Aβ deposition was associated with changes in autophagy activity. APP/PS1 transgenic mice were divided into transgenic sedentary (TG-SED, n=12) and transgenic exercise (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 31 publications
2
21
0
1
Order By: Relevance
“…While an increase in LC3II expression typically is thought to be associated with upregulation of autophagy, when it accumulates in concert with increases in SQSTM1/p62, it is indicative of a decrease in degradation of autophagosomal substrates (Yoshii and Mizushima, 2017). Furthermore, Zhao et al (2018) argue that the elevated LAMP1 in APP/PS1 mice suggests an accumulation of lysosomes and reduced clearance of autophagic substrates and is consistent with prior findings in this AD model. In contrast, exercise in APP/PS1 mice led to a further increase in LC3II expression and decreases in both SQSTM1/p62 and LAMP1, which are results consistent with an increase in autophagic flux that likely explains, at least in part, the reduction in Aβ plaque accumulation.…”
Section: Exercise and Exercise Mimeticssupporting
confidence: 86%
See 2 more Smart Citations
“…While an increase in LC3II expression typically is thought to be associated with upregulation of autophagy, when it accumulates in concert with increases in SQSTM1/p62, it is indicative of a decrease in degradation of autophagosomal substrates (Yoshii and Mizushima, 2017). Furthermore, Zhao et al (2018) argue that the elevated LAMP1 in APP/PS1 mice suggests an accumulation of lysosomes and reduced clearance of autophagic substrates and is consistent with prior findings in this AD model. In contrast, exercise in APP/PS1 mice led to a further increase in LC3II expression and decreases in both SQSTM1/p62 and LAMP1, which are results consistent with an increase in autophagic flux that likely explains, at least in part, the reduction in Aβ plaque accumulation.…”
Section: Exercise and Exercise Mimeticssupporting
confidence: 86%
“…SQSTM1/p62 is degraded during autophagy, so a decrease in protein levels is generally associated with elevated autophagic flux, while SQSTM1/p62 accumulation is indicative of autophagy impairment. Zhao et al (2018) found that exercise reduced Aβ plaque deposition in the APP/PS1 transgenic model of AD, which has reduced autophagy activity relative to wild-type mice as indicated by the combination of increases in LC3II and SQSTM1/p62, as well as an overabundance of the lysosomal protein LAMP1. While an increase in LC3II expression typically is thought to be associated with upregulation of autophagy, when it accumulates in concert with increases in SQSTM1/p62, it is indicative of a decrease in degradation of autophagosomal substrates (Yoshii and Mizushima, 2017).…”
Section: Exercise and Exercise Mimeticsmentioning
confidence: 95%
See 1 more Smart Citation
“…In addition, expression of other genes linked to AD progression such as β-site APP-cleaving enzyme 1 (BACE1), presenilin 1 (PS1), insulin-degrading enzyme (IDE), tau, and the receptor for advanced glycation end products (RAGE) are reduced as a consequence of exercise [ 22 , 23 ]. This may be due to a decrease in lipid-raft formation [ 23 ], activation of SIRT1 (sirtuin (silent mating type information regulation 2 homolog) 1) [ 12 , 24 ], and an increase in autophagy [ 19 , 25 ]. In addition, exercise has been proposed to mitigate mitochondrial dysfunction [ 11 , 26 ], delay disease-related white matter volume loss [ 27 30 ], reduce neuroinflammation [ 19 , 21 , 22 , 31 34 ] and oxidative stress [ 10 , 19 , 35 ], repress neuronal cell death [ 36 ], and favor adult neurogenesis [ 17 , 37 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, exercise using treadmill showed a significant decline in oxidative stress and Aβ levels in the hippocampus of an AD rodent model [ 396 - 400 ]. Moreover, physical activity also increased autophagy and improved learning and memory in an AD mouse model [ 399 , 400 ]. Additionally, swimming and running wheels were reported to not only decrease Aβ levels but also improve cognition and motor activity in an AD rodent model [ 401 - 403 ].…”
Section: Resultsmentioning
confidence: 99%